PMMA (polymethyl methacrylate) coated diaphragm as well as preparation method and application thereof

By coating the surface of PMMA spheres with dopamine or a mixture of dopamine and AHPS, ensuring that PMMA spheres are arranged in a single layer in the coating, the problem of uneven distribution of PMMA particles is solved, and the uniformity of the coating and the improvement of lithium ion transmission efficiency are achieved.

CN119812670APending Publication Date: 2025-04-11NINGDE ZHUOGAO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411644483.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The PMMA particles are unevenly distributed on the lithium battery separator, hindering the transmission efficiency of lithium ions and causing inconsistent coating thickness, affecting the battery's energy and breathability performance.

Method used

By coating the surface of the PMMA spheres with dopamine or a mixture of dopamine and AHPS, it is ensured that the PMMA spheres are arranged in a single layer in the coating with a diameter of approximately equal to the thickness of the coating, thereby forming a uniform stripe-like coating.

Benefits of technology

The uniformity of the coating and single-layer spreading are achieved, the coating usage is reduced, the lithium ion transmission efficiency and the energy density of the battery are improved, and the liquid absorption capacity of the battery cell is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812670A_ABST
    Figure CN119812670A_ABST
Patent Text Reader

Abstract

The invention discloses a PMMA (polymethyl methacrylate) coated diaphragm as well as a preparation method and application thereof, and relates to the technical field of secondary batteries. The coated diaphragm comprises: a base film, which is a porous thin film; the coating is arranged on at least one side surface of the base film, the coating comprises a coating area and a non-coating area, the coating area and the non-coating area are arranged at an interval, and the coating area is strip-shaped; the coating comprises PMMA small balls, a thickening agent and a binder, the PMMA small balls are coated with dopamine or a mixture of dopamine and AHPS, and the PMMA small balls are arranged in a single layer. The problems that the PMMA particles are not uniformly distributed and the transmission efficiency of lithium ions is hindered are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a PMMA-coated diaphragm and a preparation method and application thereof. Background Art

[0002] With the development of the market, the rapid development of electronic products and new energy products, the requirements for lithium-ion batteries are getting higher and higher. Among them, lithium-ion battery separators with excellent performance are very important for improving the comprehensive performance of lithium batteries. In the preparation process of the battery cell, the organic coating on the surface of the separator is an important guarantee for the formation of hard batteries. Due to its corrosion resistance, easy adhesion, and liquid retention, PVDF is widely used as a glue layer in lithium battery separators to increase the adhesion between the separator and the pole piece, thereby ensuring the hardness of the battery. However, as people's requirements for the adhesion between the separator and the pole piece become higher and higher, the adhesion between pure PVDF and the pole piece does not meet the requirements. PMMA is widely used in lithium batteries because of its excellent adhesion. However, if the spraying process is adopted, PMMA forms discrete isolated points of different thicknesses on the separator, and the uniformity is poor; using the gravure roller full coating process, the densely laid PMMA balls will hinder the transmission efficiency of lithium ions to a certain extent. During the hot pressing stage, the PMMA balls are deformed, and the distance between adjacent balls becomes smaller, which significantly increases the air permeability of the separator. Summary of the invention

[0003] The purpose of the present application is to provide a PMMA coated diaphragm and a preparation method and application thereof, so as to solve the problem that PMMA particles are unevenly distributed and hinder the transmission efficiency of lithium ions.

[0004] To achieve the above-mentioned purpose, the embodiment of the present application adopts the following technical scheme: a PMMA coated diaphragm, comprising: a base film, the base film is a porous film; a coating, the coating is arranged on at least one side of the surface of the base film, the coating includes a coating area and a non-coating area, the coating area and the non-coating area are arranged at intervals, and the coating area is strip-shaped; the coating includes PMMA beads, a thickener and a binder, the PMMA beads are coated with dopamine or a mixture of dopamine and AHPS, and the PMMA beads are arranged in a single layer.

[0005] In the above technical scheme, the embodiment of the present application ensures that the PMMA beads in the coating area are arranged in a single layer by coating the surface of the PMMA beads with dopamine or a mixture of dopamine and AHPS, and the diameter Dv50 is approximately equal to the thickness D of the coating. While ensuring that the diaphragm and the pole piece have high adhesion, the amount of coating can be greatly reduced, and the reduction in coating thickness is also beneficial to the improvement of battery energy and lithium ion transmission efficiency. Compared with the spraying process, the uniformity of the coating thickness is effectively guaranteed, and the gap twill has a capillary adsorption effect, which increases the liquid absorption of the battery core. Under the premise of meeting the high adhesion, the non-coating area of ​​the right proportion can further reduce the amount of coating and reduce the obstruction to ion transmission. The dopamine / AHPS wrapped in the outer layer of the PMMA beads effectively ensures the single-layer spreading and striped formation of the coating.

[0006] Further, according to an embodiment of the present application, the particle size of the PMMA beads is 0.1 to 5.0 μm.

[0007] Further, according to an embodiment of the present application, the thickener is one or more of carboxymethyl cellulose, carboxyethyl cellulose, polyacrylamide, guar gum, polyethylene oxide, sodium alginate, pinene alcohol, polyvinyl alcohol, polyacrylic acid or polyurethane.

[0008] Further, according to an embodiment of the present application, the adhesive is one or more of polyacrylate, polyurethane acrylate, polyether acrylate, polyurethane or epoxy resin.

[0009] Further, according to an embodiment of the present application, the width of the coating area is 0.05 to 10 mm.

[0010] Further, according to an embodiment of the present application, the width of the non-coating area is 0.05 to 10 mm.

[0011] Further, according to an embodiment of the present application, the angle between the coating area and the MD direction of the base film is 10 to 80° or 100 to 170°.

[0012] Further, according to an embodiment of the present application, the effective coverage of the coating area is 10 to 90%.

[0013] In order to achieve the above object, the present application also discloses a method for preparing a PMMA-coated diaphragm, comprising the following steps:

[0014] Preparation of the PMMA beads: dissolving dopamine or dopamine and AHPS in deionized water, and adjusting the pH to 8.5 with LiOH to obtain dispersion liquid 1; adding PMMA dispersion liquid with a solid content of 25% to dispersion liquid 1, stirring for 24 hours at room temperature, and soaking in deionized water for 1 hour, and drying to obtain the PMMA beads;

[0015] Prepare coating slurry: add the PMMA beads to deionized water and stir thoroughly for 0.5h, add thickener and stir for 1h, then add binder and stir for 0.2-1h to obtain the coating slurry;

[0016] The coated diaphragm is prepared by coating the coating slurry on one side or both sides of the base film using a plate roller having a coating area and a non-coating area, and then curing and drying to form stripe patterns.

[0017] In order to achieve the above-mentioned purpose, the embodiments of the present application also disclose an application of a PMMA-coated diaphragm in a secondary battery.

[0018] Compared with the prior art, the present application has the following beneficial effects: the present application ensures that the PMMA beads in the coating area are arranged in a single layer by coating the surface of the PMMA beads with dopamine or a mixture of dopamine and AHPS, and the diameter Dv50 is approximately equal to the thickness D of the coating. While ensuring that the diaphragm and the pole piece have high adhesion, the amount of coating can be greatly reduced, and the reduction in coating thickness is also beneficial to the improvement of battery energy and lithium ion transmission efficiency. Compared with the spraying process, the uniformity of the coating thickness is effectively guaranteed, and the gap twill has a capillary adsorption effect, which increases the liquid absorption of the battery core. Under the premise of meeting the high adhesion, the non-coating area of ​​the right proportion can further reduce the amount of coating and reduce the obstruction to ion transmission. The dopamine / AHPS wrapped in the outer layer of the PMMA beads effectively ensures the single-layer spreading and stripe formation of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present application is further described below in conjunction with the accompanying drawings and embodiments.

[0020] Figure 1 It is a schematic diagram of the distribution of the coated area and the non-coated area of ​​the coating in this application. DETAILED DESCRIPTION

[0021] In order to make the purpose and technical solution of the present invention clearly and completely described, and the advantages more clearly understood, the embodiments of the present invention are further described in detail with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are part of the embodiments of the present invention, rather than all of the embodiments, and are only used to explain the embodiments of the present invention, and are not used to limit the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In the description of the present invention, it should be noted that the terms "center", "middle", "upper", "lower", "left", "right", "inner", "outer", "top", "bottom", "side", "vertical", "horizontal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "one", "first", "second", "third", "fourth", "fifth", "sixth" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0023] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0024] For the purpose of simplicity and illustration, the principles of the embodiments are mainly described by reference to examples. In the following description, many specific details are proposed to provide a thorough understanding of the embodiments. However, it is obvious that for those of ordinary skill in the art, these embodiments may not be limited to these specific details in practice. In some instances, known methods and structures are not described in detail to avoid making these embodiments unnecessarily difficult to understand. In addition, all embodiments can be used in combination with each other.

[0025] The present application discloses a PMMA coated diaphragm, comprising a base film and a coating disposed on at least one side of the base film. The base film is a porous film, preferably a polyolefin film. The structure of the coating is as follows: Figure 1 As shown, it includes coated areas and non-coated areas, which are arranged at intervals. The coated areas are strip-shaped and can be parallel (or overlapping) or crossed. The morphology of a single coated stripe can be continuous or discontinuous.

[0026] Further, the above-mentioned coating includes PMMA beads, a thickener and a binder, and the PMMA beads are coated with dopamine or a mixture of dopamine and AHPS (3-allyloxy-1-hydroxy-1-propane sulfonic acid sodium salt), and the PMMA beads are arranged in a single layer. The present application ensures that the PMMA beads in the coating area are arranged in a single layer by coating the surface of the PMMA beads with dopamine or a mixture of dopamine and AHPS, and its diameter Dv50 is approximately equal to the thickness D of the coating. While ensuring that the diaphragm and the pole piece have high adhesion, the amount of coating can be greatly reduced, and the reduction in coating thickness is also conducive to the improvement of battery energy and lithium ion transmission efficiency. Compared with the spraying process, the uniformity of the coating thickness is effectively guaranteed, and the gap twill has a capillary adsorption effect, which increases the liquid absorption of the battery core. Under the premise of meeting the high adhesion, the non-coating area of ​​the appropriate proportion can further reduce the amount of coating and reduce the obstruction to ion transmission. The dopamine / AHPS wrapped in the outer layer of the PMMA beads effectively ensures the single-layer spreading and stripe formation of the coating. The particle size of the PMMA beads is 0.1-5.0 μm.

[0027] In addition, the thickener is one or more of carboxymethyl cellulose, carboxyethyl cellulose, polyacrylamide, guar gum, polyethylene oxide, sodium alginate, pinene alcohol, polyvinyl alcohol, polyacrylic acid or polyurethane. The binder is one or more of polyacrylate, polyurethane acrylate, polyether acrylate, polyurethane or epoxy resin.

[0028] For the coating area, its width is preferably 0.05-10 mm, and the width of the non-coating area is also preferably 0.05-10 mm. What needs to be guaranteed is the effective coverage, that is, (area of ​​the coating area) / (area of ​​the coating area + area of ​​the non-coating area)*100%, which ranges from 10 to 90%. The coating area is inclined relative to the base film, and the angle with the MD direction of the base film is 10 to 80° or 100 to 170°. The effective bonding force obtained in this way: under the conditions of 90°C, 2 to 4 MPa and 3 to 5 minutes of hot pressing, the bonding force between the diaphragm and the pole piece is greater than 2N / m.

[0029] Secondly, the present application also discloses a method for preparing a PMMA-coated diaphragm, comprising the following steps:

[0030] Preparation of the PMMA beads: dissolving dopamine or dopamine and AHPS in deionized water, and adjusting the pH to 8.5 with LiOH to obtain dispersion liquid 1; adding PMMA dispersion liquid with a solid content of 25% to dispersion liquid 1, stirring for 24 hours at room temperature, and soaking in deionized water for 1 hour, and drying to obtain the PMMA beads;

[0031] Prepare coating slurry: add the PMMA beads to deionized water and stir thoroughly for 0.5h, add thickener and stir for 1h, then add binder and stir for 0.2-1h to obtain the coating slurry;

[0032] The coated diaphragm is prepared by coating the coating slurry on one side or both sides of the base film using a plate roller having a coating area and a non-coating area, and then curing and drying to form stripe patterns.

[0033] Wherein, if a mixture of AHPS and dopamine is added, the mass ratio of AHPS to dopamine is 10:1. The amount of PMMA dispersion added is 10-100 parts by mass, and dispersion one is 1000 parts by mass. The concentration of dispersion one is 0.5g / L~5g / L, and the thickness of the coating layer outside the PMMA beads is 1~10nm. The solid content of the coating slurry is 2~20wt%, of which PMMA beads account for 60%~85% of the total solid content. The thickness of the polyolefin base film is 5~20μm, and the porosity is 30%~80%.

[0034] The technical effects of the present application are illustrated below by listing Examples 1-6 and Comparative Examples 1-2, but the present application is not limited to these Examples.

[0035] [Example 1]

[0036] Step 1: Preparation of PMMA beads:

[0037] Step 1.1) Dissolve 1.5 parts of dopamine and 15 parts of AHPS respectively in 1000 parts of deionized water, and adjust the pH to 8.5 with LiOH to obtain dispersion 1;

[0038] Step 1.2) Add 80 parts of PMMA dispersion with a solid content of 25% into dispersion 1, stir thoroughly for 24 hours at room temperature, soak in deionized water for 1 hour, and obtain PMMA beads after drying.

[0039] Step 2, add 20 parts of PMMA beads with an average diameter of 600nm and an average coating thickness of 3nm to 300 parts of deionized water, stir thoroughly for 0.5h at room temperature, add 100 parts of carboxymethyl cellulose (CMC) dispersion with a solid content of 2% and stir thoroughly for 1h, then add 2 parts of polyacrylate (ACM) with a solid content of 50% and stir for 0.5h to obtain a dispersed and stable coating slurry;

[0040] Step 3: Use a micro-gravure with a coating area of ​​0.4 mm and a non-coating area of ​​1.6 mm and a stripe angle of 45° to apply the coating slurry to one side of a 7 μm polyethylene separator, and after curing and drying, the overall coating weight is 0.15 g / m 2 .

[0041] [Example 2]

[0042] In this example, the "1.5 parts and 15 parts of dopamine and AHPS" in step 1 is adjusted to "16.5 parts of dopamine", and the rest is consistent with Example 1.

[0043] [Example 3]

[0044] In this embodiment, the "coating area and non-coating area are 0.4mm and 1.6mm respectively" of the step 3 micro-gravure is adjusted to "coating area and non-coating area are 0.2mm and 1.8mm respectively"; "the overall coating weight is 0.15g / m 2 "Adjusted to" Overall coating weight is 0.08g / m 2 ", and the rest is consistent with Example 1.

[0045] [Example 4]

[0046] In this embodiment, the "coating area and non-coating area of ​​the micro-gravure in step 3 are 0.4 mm and 1.6 mm respectively" is adjusted to "coating area and non-coating area are 0.6 mm and 1.4 mm respectively"; "the overall coating weight is 0.15 g / m2" is adjusted to "the overall coating weight is 0.22 g / m2". Others are consistent with Example 1.

[0047] [Example 5]

[0048] In this embodiment, the "coating area and non-coating area of ​​step 3 micro-gravure are 0.4mm and 1.6mm respectively" is adjusted to "coating area and non-coating area are 1.0mm and 1.0mm respectively"; "the overall coating weight is 0.15g / m 2 "Adjusted to" Overall coating weight is 0.37g / m 2 ". The rest is consistent with Example 1.

[0049] [Example 6]

[0050] In this embodiment, the "coating area and non-coating area of ​​step 3 micro-gravure are 0.4mm and 1.6mm respectively" is adjusted to "coating area and non-coating area are 9.0mm and 1.0mm respectively"; "the overall coating weight is 0.15g / m 2 "Adjusted to" Overall coating weight is 0.70g / m 2 ". The rest is consistent with Example 1.

[0051] [Example 7]

[0052] In this embodiment, step 2 "PMMA beads with an average diameter of 600 nm and an average coating thickness of 3 nm" is adjusted to "PMMA beads with an average diameter of 100 nm and an average coating thickness of 3 nm." The rest is consistent with embodiment 1.

[0053] [Example 8]

[0054] In this embodiment, step 2 "PMMA beads with an average diameter of 600 nm and an average coating thickness of 3 nm" is adjusted to "PMMA beads with an average diameter of 5 μm and an average coating thickness of 3 nm. Step 3 "the overall coating weight is 0.15 g / m 2 "Adjusted to" overall coating weight is 1.0g / m 2 "Other details are consistent with Example 1.

[0055] [Comparative Example 1]

[0056] Step 1, adding 80 parts of PMMA beads with an average diameter of 600 nm and a solid content of 25% to 240 parts of deionized water, and stirring them at room temperature for 0.5 h to obtain dispersion 1;

[0057] Step 2, adding 100 parts of a carboxymethyl cellulose (CMC) dispersion having a solid content of 2% into the dispersion 1 and stirring for 1 hour to obtain a dispersion 2;

[0058] Step 3, adding 2 parts of polyacrylate (ACM) with a solid content of 50% to the dispersion 2, stirring for 0.5h, to obtain a functional slurry with a stable dispersion;

[0059] Step 4: Use a micro-gravure with a coating area of ​​0.4 mm and a non-coating area of ​​1.6 mm and a stripe angle of 45° to coat the functional slurry on one side of the 7 μm polyethylene diaphragm, and then cure and dry it. The overall coating weight is 0.25 g / m 2 .

[0060] [Comparative Example 2]

[0061] In this comparative example, "80 parts of PMMA beads with an average diameter of 600 nm and a solid content of 25%" in step 1 are replaced by "20 parts of PVDF with an average diameter of 600 nm". The rest is the same as in comparative example 1.

[0062] [Comparative Example 3]

[0063] In this embodiment, the "coating area and non-coating area are 0.4mm and 1.6mm respectively" of the micro-gravure in step 3 is adjusted to "coating area and non-coating area are 0.1mm and 0.9mm respectively"; "the overall coating weight is 0.15g / m 2 "Adjusted to" Overall coating weight is 0.08g / m 2 ", and the rest is consistent with Example 1.

[0064] [Comparative Example 4]

[0065] In this embodiment, the "coating area and non-coating area are 0.4mm and 1.6mm respectively" of the step 3 micro-gravure is adjusted to "coating area and non-coating area are 1.0mm and 9.0mm respectively"; "the overall coating weight is 0.15g / m 2 "Adjusted to" Overall coating weight is 0.08g / m 2 ", and the rest is consistent with Example 1.

[0066] [Comparative Example 5]

[0067] In this embodiment, the "coating area and non-coating area of ​​step 3 micro-gravure are 0.4mm and 1.6mm respectively" is adjusted to "coating area and non-coating area are 0.9mm and 0.1mm respectively"; "the overall coating weight is 0.15g / m 2 "Adjusted to" Overall coating weight is 0.70g / m 2 ". The rest is consistent with Example 1.

[0068] [Comparative Example 6]

[0069] In this embodiment, the "stripe angle of 45°" of the micro-engraved plate in step 3 is adjusted to "stripe angle of 10° or 170°". The rest is the same as in embodiment 1.

[0070] [Comparative Example 7]

[0071] In this embodiment, the "stripe angle of 45°" of the micro-engraved plate in step 3 is adjusted to "stripe angle of 80° or 100°". Others are the same as in embodiment 1.

[0072] The air permeability and coating uniformity of the diaphragms prepared in the above-mentioned embodiments and comparative examples are compared below.

[0073] Air permeability: Prepare two groups (Group A and Group B) of diaphragms of Examples 1-8 and Comparative Examples 1-7. The diaphragms of Group A are not specially treated, and the diaphragms of Group B are treated as follows: Take one uncoated diaphragm and one of the examples or comparative examples, align the coated surface of the example or comparative example diaphragm with one of the uncoated diaphragms, and hot press for 3 minutes at 90°C and 2.5MPa. And use Wang Yan type air permeability meter EG01-55-1MR to test the air permeability of the diaphragm. Principle: The time required for 100mL of gas to pass through a fixed area diaphragm. Specific test results are shown in Table 1.

[0074]

[0075] As shown in Table 1, the test comparison results of Group A are as follows: Comparing the air permeability values ​​of Example 1 and Comparative Examples 1-2, the reason why the air permeability value of Comparative Example 1-2 is slightly larger is that it is caused by the multi-layer stacking of PVDF or PMMA. Air permeability value: Example 6>Example 5>Example 4>Example 1>Example 3, which is caused by the increase in coating coverage. Air permeability value: Example 7>Example 1≈Example 8, which is caused by the stacking of small-particle PMMA, resulting in a more significant increase in permeability. Air permeability value: Example 3≈Comparative Example 3≈Comparative Example 4, and the coating coverage of the three is the same. Air permeability value: Example 3≈Comparative Example 6≈Comparative Example 7, and the twill angle does not affect the air permeability value of the diaphragm. The test comparison results of Group B: The air permeability values ​​of Example 6 and Comparative Example 5 increased most significantly, indicating that the coating method with a high coverage ratio will seriously lead to an increase in the coating permeability value after hot pressing treatment.

[0076] Coating uniformity: Prepare the diaphragms of Examples 1-8 and Comparative Examples 1-7. At the coating-containing part of each group of diaphragms of the examples, use a sub-ion beam to randomly cut the cross-sections of 6 diaphragms. After the samples are treated with gold spraying, use SEM to observe the stacking of the coating beads at the interface. The specific test results are shown in Table 2.

[0077] Table 2

[0078]

[0079] As shown in Table 2, the maximum stacking number of the coated beads in Examples 1, 3-6, 8 and Comparative Examples 3-7 is 1, indicating that the PMMA beads have better spreadability on the polyolefin diaphragm after being modified with dopamine / AHPS. In Example 2, some beads have a stacking number of 2, indicating that the spreadability of PMMA modified with dopamine alone is slightly insufficient. The number of layers in Example 7 fluctuates between 4 and 6 layers, which is caused by the stacking of small-particle PMMA.

[0080] The separators prepared in the above-mentioned embodiments and comparative examples were bonded to the positive electrode plates to test their bonding strength.

[0081] Preparation of positive electrode sheet: lithium manganese oxide, polyvinylidene fluoride, acetylene black and NMP are mixed and stirred to prepare slurry, which is then coated on both sides of aluminum foil and dried to obtain the positive electrode sheet.

[0082] Dry pressing: stack the positive electrode sheet, separator, positive electrode sheet, and separator in order to 4 layers (41mm*60mm), and hot press at 90℃, 2MPa, and 3min. After cooling, perform the peeling force test between the separator and the electrode sheet. The results are shown in Table 3.

[0083] Table 3

[0084]

[0085]

[0086] The composite separators of the above-mentioned Examples 1-8 and Comparative Examples 1-7 were used together with the ternary positive electrode sheet and the graphite negative electrode sheet by adopting a winding process to prepare soft-package lithium-ion batteries, and the cycle performance test was carried out.

[0087] Cycle performance test: At a constant temperature of 25°C and a voltage range of 2.75 to 4.2V, the lithium-ion battery was discharged at a constant current of 0.2C, and the discharge capacity at different discharge rates was recorded. The results are shown in Table 4.

[0088] Table 4

[0089] project 0 laps 300 laps 600 laps Example 1 100.0% 93.6% 88.6% Example 2 100.0% 91.9% 86.9% Example 3 100.0% 94.2% 81.6% Example 4 100.0% 92.5% 87.9% Example 5 100.0% 91.1% 86.3% Example 6 100.0% 89.6% 81.8% Example 7 100.0% 88.9% 79.6% Example 8 100.0% 94.3% 85.5% Comparative Example 1 100.0% 89.2% 75.3% Comparative Example 2 100.0% 86.1% 69.6% Comparative Example 3 100.0% 94.0% 82.4% Comparative Example 4 100.0% 94.1% 80.2% Comparative Example 5 100.0% 90.3% 82.3% Comparative Example 6 100.0% 93.7% 88.3% Comparative Example 7 100.0% 93.4% 88.8%

[0090] Although the above describes the illustrative specific implementation methods of the present application so that technicians in this technical field can understand the present application, the present application is not limited to the scope of the specific implementation methods. For ordinary technicians in this technical field, as long as various changes are within the spirit and scope of the present application defined and determined by the attached claims, all application creations using the concept of the present application are protected.

Claims

1. A PMMA coated diaphragm, characterized in that: include: A basement membrane, wherein the basement membrane is a porous film; A coating, wherein the coating is disposed on at least one side of the surface of the base film, the coating comprises a coating area and a non-coating area, the coating area and the non-coating area are disposed at intervals, and the coating area is in a strip shape; The coating comprises PMMA beads, a thickener and a binder. The PMMA beads are coated with dopamine or a mixture of dopamine and AHPS, and the PMMA beads are arranged in a single layer.

2. A PMMA coated diaphragm according to claim 1, characterized in that: The PMMA beads have a particle size of 0.1-5.0 μm.

3. A PMMA coated diaphragm according to claim 1, characterized in that: The thickener is one or more of carboxymethyl cellulose, carboxyethyl cellulose, polyacrylamide, guar gum, polyethylene oxide, sodium alginate, pinene alcohol, polyvinyl alcohol, polyacrylic acid or polyurethane.

4. A PMMA coated diaphragm according to claim 1, characterized in that: The binder is one or more of polyacrylate, polyurethane acrylate, polyether acrylate, polyurethane or epoxy resin.

5. A PMMA coated diaphragm according to claim 1, characterized in that: The width of the coating area is 0.05-10 mm.

6. A PMMA coated diaphragm according to claim 1, characterized in that: The width of the non-coating area is 0.05-10 mm.

7. A PMMA coated diaphragm according to claim 1, characterized in that: The angle between the coating area and the MD direction of the base film is 10-80° or 100-170°.

8. The PMMA coated diaphragm according to claim 1, characterized in that: The effective coverage of the coating area is 10-90%.

9. A method for preparing a PMMA coated diaphragm as claimed in claim 1, characterized in that: The following steps are involved: Preparation of the PMMA beads: dissolving dopamine or dopamine and AHPS in deionized water, and adjusting the pH to 8.5 with LiOH to obtain dispersion liquid 1; adding PMMA dispersion liquid with a solid content of 25% to dispersion liquid 1, stirring for 24 hours at room temperature, and soaking in deionized water for 1 hour, and drying to obtain the PMMA beads; Prepare coating slurry: add the PMMA beads to deionized water and stir thoroughly for 0.5h, add thickener and stir for 1h, then add binder and stir for 0.2-1h to obtain the coating slurry; The coated diaphragm is prepared by coating the coating slurry on one side or both sides of the base film using a plate roller having a coating area and a non-coating area, and then curing and drying to form stripe patterns.

10. Use of the PMMA coated diaphragm according to any one of claims 1 to 8 or the PMMA coated diaphragm prepared by the preparation method of the PMMA coated diaphragm according to claim 9 in a secondary battery.